2020
DOI: 10.18196/ijief.3236
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Issues on Cash Waqf: A Thematic Literature Review

Abstract: This paper presents the most recent works on cash Waqf, focusing on identifying contemporary scholars' work in this area, providing a novel framework to indicate the existing gap, subsequently, it opens the door wider for new research commitment. This research adopts the paradigm of qualitative approach research, based on disk-based research. Google Scholar was employed, searching through the passage. Only contemporary English documents within the period of 2002-2019 were the subject of this study. Lately, cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 21 publications
0
45
0
2
Order By: Relevance
“…Waqf issues have taken this significant place due to the efforts have been done by contemporary scholars, revealing the benefits associated with Waqf practices including its applications in contemporary society plus addressing associated challenges. Most of the previous studies found that cash waqf is an efficient instrument that can be an alternative to poverty alleviation, because these initiatives require huge funds that cannot be obtained in total by the government (Aldeen et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Waqf issues have taken this significant place due to the efforts have been done by contemporary scholars, revealing the benefits associated with Waqf practices including its applications in contemporary society plus addressing associated challenges. Most of the previous studies found that cash waqf is an efficient instrument that can be an alternative to poverty alleviation, because these initiatives require huge funds that cannot be obtained in total by the government (Aldeen et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Supervision from the government, the Indonesian Waqf Board and the general public is urgently needed. So that in the future CWLS will be able to become a safe, productive and recognized model for cash waqf to support sustainable development goals (SDGs) (Aldeen et al, 2020;Musari, 2019) which is able to bring mashlahah who are able to maintain syara' goals and achieve maximum benefit for the people.…”
Section: Issues In Product Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The mainstream economy is suffering from a lack of realism, lack of balance lack of moral screening; these are the effect of financialization (Aldeen, Ratih, & Herianingrum, 2020). The financial contribution to the economy has been increased drastically, especially in the second half of the last century.…”
Section: Article Infomentioning
confidence: 99%